In vivo regulation of chromatin dynamics by Saccharomyces cerevisiae histone chaperone Nap1 - Barker, Kristi Leigh, author; Stargell, Laurie A., advisor; Luger, Karolin, committee member; Wilusz, Carol J., committee member (Colorado State University. Libraries, 2011)
Eukaryotic cells must organize massive amounts of DNA into the nucleus. In order to accomplish this, the DNA must be compacted into a highly ordered structure known as chromatin. The basic, repeating unit of chromatin is the nucleosome, which consists of two copies of each histone (H2A, H2B, H3 and H4) and organizes 147 base pairs of DNA. Due to its highly compact nature, nucleosomes must be removed during gene expression in order for the transcription machinery to access the DNA. Shuttling of nucleosomes on and off DNA is mediated by a group of proteins known as histone chaperones. Importantly, histone chaperones interact with another family of chromatin remodeling complexes known as histone acetyltransferases (HATs). Acetylation of histones is correlated with the active transcription of genes. The work presented here explores the dynamics and kinetics of histone H3 occupancy and acetylation of histone H3-K9 and H3-K14 in a wild-type strain and strains deleted for three known histone chaperones (Nap1, Vps75 and Asf1) of the yeast Saccharomyces cerevisiae at the well characterized galactose inducible genes. This data offers insight into the epigenetic regulation of chromatin as well as possible mechanisms for the histone chaperones surveyed.